1989
DOI: 10.2165/00003088-198917050-00002
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Implications for the Clinical Use of Propofol

Abstract: Propofol, the recently marketed intravenous induction agent for anaesthesia, is chemically unrelated to earlier anaesthetic drugs. This highly lipophilic agent has a fast onset and short, predictable duration of action due to its rapid penetration of the blood-brain barrier and distribution to the CNS, followed by redistribution to inactive tissue depots such as muscle and fat. On the basis of pharmacokinetic-pharmacodynamic modelling, a mean blood-brain equilibration half-life of only 2.9 minutes has been cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
129
2
3

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(136 citation statements)
references
References 41 publications
2
129
2
3
Order By: Relevance
“…The pharmacokinetic properties of MDL and PRO (18)(19)(20)(21) suggest that these agents may be advantageous for terminating seizures more quickly than PTB. Data in our systematic review were not sufficient to compare this important outcome variable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pharmacokinetic properties of MDL and PRO (18)(19)(20)(21) suggest that these agents may be advantageous for terminating seizures more quickly than PTB. Data in our systematic review were not sufficient to compare this important outcome variable.…”
Section: Discussionmentioning
confidence: 99%
“…MDL (a 1,4-benzodiazepine belonging to the 1,2-anelated subgroup) is a fast-acting water-soluble benzodiazepine (BZD) with a half-life of 1.2 to 12.3 h (18,19). PRO (2,6-diisopropylphenol) is a very fast acting agent with a second exponential phase half-life of 34 to 56 min, reflecting its high rate of metabolic clearance, and a third-phase half-life of 184 to 480 min (20). PTB (sodium-5-ethyl-5,1-methylbutyl barbiturate) is a barbiturate with onset of action after 15-20 min and a half-life of 15-60 h (21).…”
mentioning
confidence: 99%
“…Propofol is lipophilic and is rapidly distributed into tissues and metabolized following the cessation of intravenous administration, a fact that explains why sedation is short-lived (22,57,58). It is possible that metabolites of propofol that persist within tissues for several days lead to the suppression of host immunity against microbial infection.…”
Section: Discussionmentioning
confidence: 99%
“…Propofol also provided significantly better patient cooperation than midazolam. 12,13 However, this agent occasionally decreases systemic vascular resistance, cardiac contractility, and ultimately cardiac output without a concomitant change in heart rate, and respiratory depression can also occur. 5,14,15 Recently, several studies have revealed most adverse events associated with propofol sedation were mild and often transient during advanced interventional endoscopic procedure.…”
Section: Discussionmentioning
confidence: 99%